Overall tumor genomic instability: an important predictor of recurrence-free survival in patients with localized clear cell renal cell carcinoma. Issue 5 (3rd May 2020) - Correa, Andres F.; Ruth, Karen J.; Al-Saleem, Tahseen; Pei, Jianming; Dulaimi, Essel; Kister, Debra; Collins, Michelle; Abbosh, Phillip H.; Slifker, Michael J.; Ross, Eric; Uzzo, Robert G.; Testa, Joseph R.
ABSTRACT: Measurement of a tumor's overall genomic instability has gathered recent interest over the identification of specific genomic imbalances, as it may provide a more robust measure of tumor aggressiveness. Here we demonstrate the association of tumor genomic instability in the prediction of disease recurrence in patients with clinically localized clear cell renal cell carcinoma (ccRCC). Genomic copy number analysis was performed using SNP-based microarrays on tumors from 103 ccRCC patients. The number of copy number alterations (CNAs) for each tumor was calculated, and a genomic imbalance threshold (GIT) associated with high stage and high-grade disease was determined. Cox proportional hazards regression analyzes were performed to assess the effect of GIT on recurrence-free survival adjusting for known confounders. In the cohort, copy number losses in chromosome arms 3p, 14q, 6q, 9p, and 1p and gains of 5q and 7p/q were common. CNA burden significantly increased with increasing stage ( p < .001) and grade ( p < .001). The median CNA burden associated with patients presenting with advanced stage (IV) and high-grade (III/IV) tumors was ≥9, defining the GIT. On regression analysis, GIT was a superior predictor of recurrence (Hazard Ratio 4.44 [CI 1.36–14.48], p = .01) independent of stage, with similar results adjusting for grade. These findings were confirmed using an alternative measure of genomic instability, weighted Genomic Integrity Index. Our data support a key role for genomic instability in ccRCC progression. More importantly, we have identified a GIT (≥ 9 CNAs) that is a superior and independent predictor of disease recurrence in high-risk ccRCC patients.